Risk Factors of Subclinical Atherosclerosis and Plaque Burden in High Risk Individuals: Results From a Community-Based Study - Bian, Lianduo; Xia, Lili; Wang, Yixin; Jiang, Jiajia; Zhang, Yonghui; Li, Dongxue; Li, Wei; He, Yan (Frontiers in Physiology, 2018)
China is going through major change and the incidence of first-ever stroke has increased dramatically. In this study, we aim to determine the ultrasound characteristics of carotid intima-media thickness and carotid plaques in the Chinese community-based population with high risk of stroke. 1009 stroke-free participants from Datun community were classified at high risk of stroke and included in this cross-sectional study. We performed B-mode carotid ultrasound imaging in all of the study subjects to measure the carotid intima-media thickness in the common carotid artery far wall and carotid plaques in the common carotid artery, bifurcation and internal carotid artery. Stepwise logistic regression analyses were used to determine factors associated with elevated carotid intima-media thickness and subclinical atherosclerosis, as well as plaque burden (≥2 plaques). Our results showed that traditional risk factors including aging, hypertension, current smoking and the level of high density lipoprotein cholesterol are associated with subclinical atherosclerosis and plaque burden in high-risk community residents. To improve primary prevention in this population, we may consider intense blood pressure and lipid management, and smoking cessation.